Exploring the Benefits of Early Intervention Programs for Children with Disabilities in Injibara, Ethiopia - Getachew Admassu (Journal of Research in Education and Pedagogy, 2026)
This study explores the benefits of early intervention programs (EIPs) for children with disabilities (CWDs) in primary schools within Injibara Town Administration, Ethiopia. Early intervention is globally recognized for enhancing developmental outcomes and promoting inclusion, yet in low-resource contexts like Ethiopia, systemic barriers often limit access and effectiveness. The objective of this research is to investigate the existing support structures, service delivery mechanisms, and challenges faced by CWDs in accessing early intervention, with the aim of informing inclusive policy and practice. A qualitative case study design was employed, utilizing purposive sampling to select three CWDs (with motor, visual, and learning impairments), their mothers, three school principals, and the head of a local health center. Data were gathered through semi-structured interviews, focus group discussions, and document analysis, and thematically analyzed to identify recurring patterns and insights. Key findings reveal critical systemic gaps: significant delays in disability identification, often beyond age six; a severe lack of access to EIPs due to absent rehabilitation services and insufficient teacher training; and pervasive stigma and social exclusion, exacerbated by limited awareness among families and communities. The experiences of children highlighted feelings of isolation and academic marginalization, while caregivers expressed helplessness due to poverty and informational gaps. In conclusion, the study underscores an urgent need for integrated, multi-sectoral EIPs that incorporate community-based screening, capacity building for parents and teachers, mobile rehabilitation units, and policy reforms aligned with the UNCRPD. Recommendations include establishing local rehabilitation centers, implementing disability-inclusive education, and launching community awareness campaigns. Despite the study’s localized focus and small sample size, it provides actionable pathways for empowering CWDs and calls for immediate collaboration among government bodies, NGOs, and communities to foster equitable inclusion in low-resource settings.